Phenotypic heterogeneity in mortality and prognosis of pulmonary alveolar proteinosis: a large-scale, global pooled analysis of individual-level data - Huang, Junfeng; Xie, Shuojia; Gao, Yuewen; Lin, Zikai; Xu, Zhe; Lin, Jinsheng; He, Linzhi; Chen, Gengjia; Zheng, Ziwen; Xu, Zhixing; Chen, Jingyan; Guo, Jiaming; et al. (Orphanet journal of rare diseases, 2025)
Pulmonary Alveolar Proteinosis (PAP) is a rare interstitial lung disease with diverse clinical manifestations and outcomes. However, there are limited data on the heterogeneity of PAP, as well as its prognosis, cause of death and genetic mechanisms. This study aims to elucidate mortality, prognostic features, and genetic mechanisms in patients with PAP. The individual patient data of clinical and mortality were obtained by summarizing the published cases series. Patients with PAP were classified using K-means clustering, and logistic regression identified prognostic factors affecting outcomes. Inheritance and related mechanism of PAP were described by summarizing PAP related genes and enrichment analysis. Our analysis included 3278 patients from 295 reports, with 88.6% diagnosed with idiopathic PAP (IPAP). Twelve major categories of cause were counted from 312 deaths (mortality: 9.5%), the most common of which were respiratory failure (45.8%) and lung infections (18.3%). Three symptom-related clusters were identified, and patients with multiple symptoms appeared to have worse mortality than those with single or no symptoms (p < 0.05). Non-secondary patterns (OR 2.87, p = 0.003), whole lung lavage (OR 0.15, p < 0.001), and effective GM-CSF therapy (OR 0.08, p < 0.001) are prognostic factors associated with decreased mortality. Additionally, 134 significant genes related to PAP development were identified, highlighting the roles of immune response and lipid metabolism. This study comprehensively describes the clinical characteristics cause of death, prognosis and associated factors based on the global PAP population. The significant phenotype heterogeneity highlighting the importance of long-term prognosis and individualized management for patients with PAP.